2008
DOI: 10.1177/1753193408094440
|View full text |Cite
|
Sign up to set email alerts
|

Cold Hypersensitivity 6 To 10 Years after Replantation or Revascularisation of Fingers: Consequences for Work and Leisure Activities

Abstract: We investigated cold hypersensitivity and activity in 81 adults (male/female 76/5), 6 to 10 years after finger replantation/revascularisation (mean age at injury 43 (SD 15) years). Questionnaires included the McCabe Cold Sensitivity Severity Scale, Potential Work-Exposure Scale and the Disabilities of the Arm, Shoulder and Hand (DASH) score. Eighty per cent of the respondents were cold hypersensitive; 20% were severely or extremely cold hypersensitive. Of the 74 patients employed at injury, 7% had changed work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 36 publications
(48 reference statements)
3
17
1
Order By: Relevance
“…Cold sensitivity creates a large burden of illness, and it is poorly understood with no effective management [2,3,6,7,16,20,29]. As such, we suggest that cold sensitivity of the hand is underrepresented in the hand literature and that more concerted efforts should be made to understand and manage this problem.…”
Section: Discussionmentioning
confidence: 99%
“…Cold sensitivity creates a large burden of illness, and it is poorly understood with no effective management [2,3,6,7,16,20,29]. As such, we suggest that cold sensitivity of the hand is underrepresented in the hand literature and that more concerted efforts should be made to understand and manage this problem.…”
Section: Discussionmentioning
confidence: 99%
“…Pain may also be associated with cold sensitivity 15,27,28,[64][65][66][67][68][69][70][71][72][73][74][75][76][77][78] . The present study showed that patients with peripheral nerve injury had high levels of cold sensitivity and disability and that disability was predicted by pain and cold sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…86,87,[89][90][91][92][93][94][95][96][97][98][99][100] Several studies have supported the continuation of cold-sensitivity symptoms in patients with hand injuries and nerve injuries and following replantation. 89,91,92,97,101,102 Campbell and Kay evaluated 176 patients following hand injuries, 73% of whom reported cold-related symptoms; most of these were related to pain. 91 Graham and Schofield evaluated patients more than 2 years after hand injury; 86 most of these patients (90% of trauma cases) reported cold intolerance, and only 9% reported an improvement over time.…”
Section: Considerations Of Cold Sensitivity and Contextual (Psychosocmentioning
confidence: 99%
“…36,[86][87][88][89] The terms ''cold sensitivity'' and ''cold intolerance'' have been used interchangeably in the literature; in this review, the term ''cold sensitivity'' is used, except in cases where reference is made to published studies whose authors have used the term ''cold intolerance.'' The symptoms of cold sensitivity are often attributed to poor outcome following traumatic peripheral nerve injuries and have been reported more frequently in patients with digital amputations and replantations.…”
Section: Considerations Of Cold Sensitivity and Contextual (Psychosocmentioning
confidence: 99%